Implementation Sharia Ethics For Sharia Compliance Audit on Audit Process: Implementation Sharia Ethics For Sharia Compliance Audit on Audit Process - hasanah, ikhwah; ulfa wibowo, fitria (UMBanjarmasin, 2022)
The purpose of the company audit is to examine the accountability of financial statements based on generally accepted accounting standards. The use of audit to find out transparently and accountably a financial report. The audit is carried out by the company by involving the company's internal auditors and external auditors, this is done to avoid the auditor's bias and intervention from one of the parties. Examination of financial statements by a competent external auditor in accordance with the needs of the entity, this is inseparable from the desire of the company's management to provide information to other parties that can be used in decision making. When conducting an audit, an auditor must work professionally by adhering to the accountant's code of ethics and/or the Islamic/sharia accountant code of ethics. Audit of financial statements as a form of company compliance with the rules set by the government where the audit compliance depends on the company, whether the company uses conventional principles or based on Islamic sharia. This research uses library research where this literature study is a form of qualitative research with the object of study is library data. Library data contains thoughts and ideas that are supported by reading sources. In this case, the reading sources used are related to the topic of literature, namely audits, code of ethics for accountants/auditors, and compliance audits